(untitled) (Международный научный журнал «Инженер», 2026)
This article examines the relationship between natural gas production in Uzbekistan and the factors affecting it — domestic consumption, export volume, export income and international gas prices. A multivariate linear regression model was built to estimate the effects of these variables based on 20 years of data. Correlation analysis showed strong correlation between several indicators, while VIF analysis eliminated the multicollinearity problem. The final model was statistically evaluated for reliability using t-tests and F-tests. Through the results, factors were identified that significantly affect the volume of gas production. The conclusions drawn from these results help policymakers optimize resource management and export strategies.